Tuning the Hybridization of Local Exciton and Charge‐Transfer States in Highly Efficient Organic Photovoltaic Cells. Issue 23 (24th March 2020) - Xu, Ye; Yao, Huifeng; Ma, Lijiao; Hong, Ling; Li, Jiayao; Liao, Qing; Zu, Yunfei; Wang, Jingwen; Gao, Mengyuan; Ye, Long; Hou, Jianhui
Abstract: Decreasing the energy loss is one of the most feasible ways to improve the efficiencies of organic photovoltaic (OPV) cells. Recent studies have suggested that non‐radiative energy loss ( E non - rad loss ) is the dominant factor that hinders further improvements in state‐of‐the‐art OPV cells. However, there is no rational molecular design strategy for OPV materials with suppressed E non - rad loss . Herein, taking molecular surface electrostatic potential (ESP) as a quantitative parameter, we establish a general relationship between chemical structure and intermolecular interactions. The results reveal that increasing the ESP difference between donor and acceptor will enhance the intermolecular interaction. In the OPV cells, the enhanced intermolecular interaction will increase the charge‐transfer (CT) state ratio in its hybridization with the local exciton state to facilitate charge generation, but simultaneously result in a larger E non - rad loss . These results suggest that finely tuning the ESP of OPV materials is a feasible method to further improve the efficiencies of OPV cells. Abstract : Non‐radiative energy loss in organic photovoltaic cells can be achieved by tuning the charge‐transfer state ratio in the hybridized state with the local exciton state. The molecular electrostatic potential (ESP) is considered as a quantitative parameter. By adjusting the ESP difference between PBDB‐TF and BTP‐XF, non‐radiative energy loss is reduced from 0.23 to 0.15 eV.